Interaction of gravity waves with the QBO: A satellite perspective. Issue 5 (14th March 2014) - Ern, M.; Ploeger, F.; Preusse, P.; Gille, J. C.; Gray, L. J.; Kalisch, S.; Mlynczak, M. G.; Russell, J. M.; Riese, M.
Abstract One of the most important dynamical processes in the tropical stratosphere is the quasi‐biennial oscillation (QBO) of the zonal wind. Still, the QBO is not well represented in weather and climate models. To improve the representation of the QBO in the models, a better understanding of the driving of the QBO by atmospheric waves is required. In particular, the contribution of gravity waves is highly uncertain because of the small horizontal scales involved, and there is still no direct estimation based on global observations. We derive gravity wave momentum fluxes from temperature observations of the satellite instruments HIRDLS and SABER. Momentum flux spectra observed show that particularly gravity waves with intrinsic phase speeds <30m/s (vertical wavelengths <10km) interact with the QBO. Gravity wave drag is estimated from vertical gradients of observed momentum fluxes and compared to the missing drag in the tropical momentum budget of ERA‐Interim. We find reasonably good agreement between their variations with time and in their approximate magnitudes. Absolute values of observed and ERA‐Interim missing drag are about equal during QBO eastward wind shear. During westward wind shear, however, observations are about 2 times lower than ERA‐Interim missing drag. This could hint at uncertainties in the advection terms in ERA‐Interim. The strong intermittency of gravity waves we find in the tropics might play an important role for the formation of the QBO and may have important implications for the parameterization of gravity waves in global models.